Synthesis of high strength binders from alkali activation of glass materials from municipal solid waste incineration bottom ash - Zhu, Weiping (2021)
This study reports an innovative way to utilize municipal solid waste incineration bottom ash for cleaner production of high strength binders. By alkali activation of glass materials separated from incineration bottom ash with a mixture of sodium silicate and sodium hydroxide solutions, binders with compressive strengths as high as 70 MPa can be synthesized. Selective chemical extractions, X-ray powder diffraction, and Fourier transform infrared and solid-state nuclear magnetic resonance spectroscopies are engaged to characterize gel composition. Results show that the resultant binders contain mainly an amorphous sodium silicate gel. Nuclear magnetic resonance spectral deconvolution reveals that the sodium silicate gel possesses a higher nano-structural connectivity than the precursor glass materials in incineration bottom ash. Both the percentage and the degree of polymerization of the gel increases with increasing SiO2/Na2O ratio in the activating solution. The resulting binder can potentially be used for the production of construction materials and structural concretes. Conclusions from the current study are of environmental significance because they provide potential solutions to recover waste into resources and alleviates the needs for ash disposal.